The Effect of Health Education on the Level of Knowledge of Mothers of Toddlers Regarding Prevention of Acute Respiratory Infection in Toddlers - Agnestia, Dina Julia; Rukmana, Nova Mega; Yuliani, Eka; Putri, Dian Utama Pratiwi (Global Health Science Group, 2025)
Acute Respiratory Infection is one of the heaviest respiratory diseases that can cause death, people with Acute Respiratory Infection will suffer greatly if they are in humid, cold or too hot weather. Acute Respiratory Infection is the main disease of infant mortality and often ranks first in the morbidity rate of toddlers, early treatment of Acute Respiratory Infection disease is proven to reduce mortality. This study aims to determine the effect of health education on the level of knowledge of mothers under five regarding the prevention of Acute Respiratory Infection in toddlers in Gading Kencana Village, the working area of the West Bawang Bone Marga Health Center in 2023. This research design uses quantitative methods with a Pre-Experimental approach with a One Group Pretest – Postest Design approach with 55 respondents who are homogeneous samples and use purposive sampling techniques. Data obtained by distributing questionnaires. The results of the statistical test obtained a p-value of <0.005 which can be concluded Ha is accepted so that there is a significant difference. It is concluded that there is an influence of health education on the level of knowledge of mothers under five regarding the prevention of Acute Respiratory Infection in toddlers in Gading Kencana Village before counseling and after counseling.